An exploration of human services system contacts prior to suicide in South Carolina: an expansion of the South Carolina Violent Death Reporting System. (14th December 2006) - Weis, M A; Bradberry, C; Carter, L P; Ferguson, J; Kozareva, D
Abstract : Objective: To link South Carolina Violent Death Reporting System (SCVDRS) data with state government human services databases, enabling expanded analysis of suicide in South Carolina and providing a model for other jurisdictions. Design: The SCVDRS database compiles data from vital statistics, coroner reports, and law enforcement incident and supplemental reports. The Office of Research and Statistics, South Carolina Budget and Control Board (ORS) created a "Data Warehouse", to which a variety of state agencies and healthcare providers submit data on a regular basis. A unique identifier was used to link SCVDRS data to the Data Warehouse so that data may be analyzed on aggregate and case-specific levels. Year 2004 suicide data from SCVDRS were linked to South Carolina Uniform Billing codes from hospital in-patient and emergency room billing records, State Department of Mental Health service records, and criminal justice databases. Results: SCVDRS year 2004 suicide data are augmented by hospitalization and emergency room visit data and diagnoses; State Department of Mental Health service provision; and criminal involvement. Of the 491 suicides occurring in 2004, 282 linked with hospitalization and emergency room data, 196 linked with criminal history databases, and 91 had previous contact with the State Department of Mental Health. Conclusions: Linking SCVDRS data to additional human services databases enables greater examination of factors surrounding suicide. Results show the positive benefits of partnerships created through SCVDRS, illustrate how SCVDRS and human service databases may augment each other, and suggest practitioners should explore implementation of prevention programs in specific settings.